Positive electrode material and battery

By controlling the number of crack particles in the positive electrode material and regulating the unit cell parameters, the problem of ternary positive electrode material being prone to cracks and rupture during fast charging is solved, and higher cycle stability and rate performance are achieved.

CN119764401APending Publication Date: 2025-04-04SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411963548.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the rapid charging process, the ternary positive electrode material is prone to internal stress accumulation, resulting in cracks and ruptures, which in turn affects the cycle stability and rate performance of the battery.

Method used

By controlling the proportion of particles with cracks in the positive electrode material to be less than 10%, and the ratio of unit cell volume and unit cell parameter c/a is controlled to make it greater than 4.92, to improve crystal structure stability and lithium ion transport efficiency.

Benefits of technology

It effectively reduces particle rupture, improves the cycle stability and rate performance of the positive electrode material, and achieves efficient lithium ion transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764401A_ABST
    Figure CN119764401A_ABST
Patent Text Reader

Abstract

The chemical general formula of the positive electrode material is LixNiaCobMcO2, x is more than or equal to 0.98 and less than or equal to 1.1, a is more than or equal to 0.8 and less than or equal to 0.98, b is more than or equal to 0 and less than or equal to 0.2, c is more than or equal to 0 and less than or equal to 0.2, a + b + c = 1, b and c are not 0 at the same time, and M is a metal element; a section SEM image of the positive electrode material is measured through a scanning electron microscope under the amplification factor of 3K, 300 particles in the section SEM image are measured randomly, and the number proportion of the particles with cracks in the section SEM image is smaller than 10%; x-ray diffraction (XRD) measurement is carried out on the positive electrode material by adopting Cu-K alpha rays, the unit cell volume # imgabs0 # of the positive electrode material, and the relationship between the unit cell parameter c of the c axis and the unit cell parameter a of the a axis of the positive electrode material meets the condition that c / a is greater than 4.92. According to the positive electrode material, the defects of a crystal structure can be reduced, the gas production phenomenon of the positive electrode material is improved, and the high-rate performance and the cycling stability are balanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to positive electrode materials and batteries. Background Art

[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, high power density, long cycle life and low self-discharge, so they are widely used in 3C electronic products, electric vehicles and energy storage. As the core component of lithium-ion batteries, positive electrode materials directly determine the operating voltage and storage capacity of the battery. Among the many positive electrode materials, ternary positive electrode materials have become the most widely used positive electrode materials in the field of lithium-ion batteries due to their advantages of high specific capacity and high voltage platform.

[0003] During fast charging, the ternary cathode material is prone to internal stress accumulation and cracking during the lithium extraction process, which in turn causes the cathode material particles to break during the cycle, increasing side reactions and intensifying gas production, leading to battery performance degradation and affecting the capacity of the cathode material. Although surface coating treatment can generally be used to maintain the interface stability of the cathode material and improve the gas production defects of the cathode material, such improvement methods cannot fundamentally solve the related defects of the cathode material and it is difficult to balance the rate performance and cycle stability of the cathode material. Summary of the invention

[0004] The present application provides a positive electrode material and a battery. The positive electrode material of the present application can reduce crystal structure defects, improve the gas generation phenomenon of the positive electrode material, and achieve a balance between high rate performance and cycle stability.

[0005] In a first aspect, the present application provides a positive electrode material, the chemical formula of the positive electrode material is Li x Ni a Co b M c O2, 0.98≤x≤1.1, 0.8≤a≤0.98, 0≤b≤0.2, 0≤c≤0.2, a+b+c=1, b and c are not 0 at the same time, M is a metal element;

[0006] A cross-sectional SEM image of the positive electrode material is measured at a magnification of 3K by a scanning electron microscope, and 300 particles in the cross-sectional SEM image are randomly measured, and the number of particles with cracks in the cross-sectional SEM image accounts for less than 10%;

[0007] The positive electrode material is subjected to XRD measurement using Cu-Kα radiation, and the unit cell volume of the positive electrode material is The relationship between the unit cell parameter c of the c-axis and the unit cell parameter a of the a-axis of the positive electrode material satisfies: c / a>4.92.

[0008] In some embodiments, the lithium-nickel mixing ratio of the positive electrode material is 1% to 4%.

[0009] In some embodiments, the lattice strain of the cathode material is < 0.1%.

[0010] In some embodiments, the M element includes at least one of Mn, Al, Ti, Zr, Ca, Mg, W, Ba, La, Ce, B, and Y.

[0011] In some embodiments, the volume particle size distribution width of the positive electrode material satisfies: 1.0≤(D 90 -D 10 ) / D 50 ≤1.5.

[0012] In some embodiments, the positive electrode material is a single crystal material, the positive electrode material includes single crystal particles, and the particle size of the single crystal particles is 1 μm to 5 μm.

[0013] In some embodiments, the specific surface area of ​​the positive electrode material is 0.4 m 2 / g~0.9m 2 / g.

[0014] In some embodiments, the tap density of the positive electrode material is ρ1 g / cm 3 , 2.0<ρ1<2.5.

[0015] In some embodiments, the compaction density of the positive electrode material is p2 g / cm 3 , 2.8≤ρ2<3.6.

[0016] In some embodiments, the gas generation value of the positive electrode material is less than or equal to 1 mL / g.

[0017] In some embodiments, a SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and 200 particles in the SEM image are randomly measured. The average size of the longest diameter of a single particle is D, the average size of the straight line side that perpendicularly bisects the longest diameter of the particle is L, and the average aspect ratio of the particles is α=D / L, 1≤α≤1.6.

[0018] In a second aspect, the present application provides a battery, comprising the positive electrode material described in the first aspect.

[0019] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:

[0020] The positive electrode material provided in the present application is prone to cracks on the surface of the positive electrode material particles due to high-temperature sintering during the preparation process. These cracks are prone to lattice deformation during the charge and discharge cycle due to the particles' deintercalation of lithium ions. The presence of cracks makes the positive electrode material particles more likely to break, resulting in aggravated side reactions between the positive electrode material and the electrolyte, and reduced cycle stability of the positive electrode material. Therefore, the present application controls the number of cracked particles in the positive electrode material to less than 10%, so that the number of cracked particles is controlled within a suitable range, which can reduce particle breakage caused by expansion stress and improve the structural stability and cycle stability of the positive electrode material particles; at the same time, the unit cell volume of the positive electrode material is controlled A smaller unit cell volume is beneficial to maintaining the stability of the crystal structure, reducing the volume change during the charge and discharge process, and improving the compressive strength and electronic conductivity of the particles. While controlling the unit cell volume V of the positive electrode material, the unit cell parameter c / a ratio of the positive electrode material is increased, so that c / a>4.92. As the c / a ratio increases, the layered structure has fewer defects, which is beneficial to the transmission of lithium ions and increases the rate, thereby compensating for the increase in the internal resistance of lithium ion transmission caused by the reduction in the unit cell volume. In this application, by controlling the unit cell volume of the positive electrode material and the number of cracks in the particles, the two are controlled in a coordinated manner, which can effectively improve the stability of the crystal structure of the positive electrode material, reduce particle breakage, and improve the cycle stability of the positive electrode material. Then, the unit cell parameter c / a of the positive electrode material is adjusted to improve the rate performance of the positive electrode material, thereby achieving a comprehensive improvement in the cycle stability and gas production of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0022] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application;

[0023] Figure 2 This is an electron microscope image of a cross section of the positive electrode material obtained in Example 1 of the present application;

[0024] Figure 3 This is an electron microscope image of a cross section of the positive electrode material obtained in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0025] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0026] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0028] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0029] The high-temperature sintering process of the positive electrode material will lead to the formation of surface cracks. The cracks will expose more active sites inside the particles to react with the electrolyte, accelerate the capacity decay of the positive electrode material, reduce the structural stability and cycle stability of the positive electrode material, and thus reduce the cycle performance of the battery.

[0030] In summary, microcracks are the main reason for the decline in the cycle performance of positive electrode materials. Cracks will destroy the structure of positive electrode materials and reduce the structural stability and cycle stability of positive electrode materials. Once cracks are formed on the surface of particles, the electrolyte will enter the interior of the positive electrode material particles along the cracks, react with the transition metal, cause the transition metal to dissolve, seriously damage the particle structure of the positive electrode material, and eventually cause the particles to break, reducing the overall structural stability and cycle performance of the positive electrode material.

[0031] In a first aspect, the present application provides a positive electrode material, wherein a cross-sectional SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and 300 particles in the cross-sectional SEM image are randomly measured, and the number of particles with cracks in the cross-sectional SEM image accounts for less than 10%;

[0032] The positive electrode material is subjected to XRD measurement using Cu-Kα radiation, and the unit cell volume of the positive electrode material is The relationship between the unit cell parameter c of the c-axis and the unit cell parameter a of the a-axis of the positive electrode material satisfies: c / a>4.92.

[0033] The positive electrode material provided in the present application is prone to cracks on the surface of the positive electrode material particles due to high-temperature sintering during the preparation process. These cracks are prone to lattice deformation during the charge and discharge cycle due to the particles' deintercalation of lithium ions. The presence of cracks makes the positive electrode material particles more likely to break, resulting in aggravated side reactions between the positive electrode material and the electrolyte, and reduced cycle stability of the positive electrode material. Therefore, the present application controls the number of cracked particles in the positive electrode material to less than 10%, so that the number of cracked particles is controlled within a suitable range, which can reduce particle breakage caused by expansion stress and improve the structural stability and cycle stability of the positive electrode material particles; at the same time, the unit cell volume of the positive electrode material is controlled A smaller unit cell volume is conducive to maintaining the stability of the crystal structure, reducing the volume change during the charge and discharge process, and improving the compressive strength and electronic conductivity of the particles. While controlling the unit cell volume V of the positive electrode material, the unit cell parameter c / a ratio of the positive electrode material is increased, so that c / a>4.92. As the c / a ratio increases, the layered structure has fewer defects, which is conducive to the transmission of lithium ions. Increase the rate, thereby compensating for the increase in the internal resistance of lithium ion transmission caused by the reduction in the unit cell volume. In this application, by controlling the unit cell volume of the positive electrode material and the number of cracks in the particles, the two are controlled in a coordinated manner, which can effectively improve the stability of the crystal structure of the positive electrode material, reduce particle breakage, and improve the cycle stability of the positive electrode material. Then, the unit cell parameter c / a of the positive electrode material is adjusted to improve the rate performance of the positive electrode material, thereby achieving a comprehensive improvement in the cycle stability and gas production of the positive electrode material. It should be noted that the cracks in this application refer to cracks with a width of less than 1um in the SEM image of the cross-section of the particles.

[0034] In some embodiments, the positive electrode material has the general chemical formula Li x Ni a Co b M c O2, 0.98≤x≤1.1, 0.8≤a≤0.98, 0≤b≤0.2, 0≤c≤0.2, a+b+c=1, b and c are not 0 at the same time, M is a metal element.

[0035] The specific value of x can be 0.98, 0.99, 1.0, 1.02, 1.04, 1.05, 1.07, 1.08, 1.09 or 1.1, and the specific value of a can be 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.92, 0.94 or 0. 98, etc., the value of b can be 0, 0.01, 0.05, 0.08, 0.09, 0.1, 0.11, 0.12, 0.15, 0.18, 0.19 or 0.2, etc., and the value of c can be 0, 0.05, 0.08, 0.09, 0.1, 0.11, 0.12, 0.15, 0.18, 0.19 or 0.2, etc., and is not limited here.

[0036] In some embodiments, the M element includes at least one of Mn, Al, Ti, Zr, Ca, Mg, W, Ba, La, Ce, B, and Y. It is understandable that an appropriate amount of M element doping can improve the lattice structure stability of the positive electrode material and reduce lithium-nickel mixing. The positive electrode material can be a nickel-cobalt-manganese oxide lithium compound or a nickel-cobalt-aluminum oxide lithium compound, which is not limited here.

[0037] In some embodiments, the number of particles with cracks in the cross-section SEM image of the positive electrode material accounts for less than 10%, which can be 9.8%, 8%, 6%, 5%, 4%, 3%, 2%, 1.5%, 1.0%, 0.5%, etc., and of course, it can also be other values ​​within the above range, which are not limited here. When the number of particles with cracks accounts for too much, the cracks will expose more active sites inside the particles to react with the electrolyte, accelerate the capacity decay of the positive electrode material, increase gas production, reduce the structural stability and cycle stability of the positive electrode material, and thus reduce the cycle performance of the battery. Preferably, the number of particles with cracks accounts for 1.5% to 9.3%. An appropriate amount of particles with cracks can cause some particles to break when the positive electrode material is pressed into a pole piece, producing some small particles, thereby increasing the compaction density of the positive electrode sheet.

[0038] In some embodiments, the positive electrode material is subjected to XRD measurement using Cu-Kα radiation, and the unit cell volume of the positive electrode material is V can be Of course, it can also be other values ​​within the above range and is not limited here.

[0039] In the present application, the unit cell volume of the positive electrode material is within the above range, the distance between transition metal atoms is shorter, and the bond energy between transition metal atoms is stronger, so that the expansion of cracks on the particle surface and extension to the interior of the particle requires overcoming a higher potential barrier, thereby inhibiting the diffusion of microcracks and improving cycle stability. However, during the process of lithium ion insertion or extraction, the lattice will expand or contract, causing stress inside the unit cell, and a smaller unit cell volume also means that it will cause greater local stress concentration, thereby promoting the diffusion of cracks during the charge and discharge process. Preferably, the present application controls Keeping the unit cell volume within an appropriate range is beneficial to maintaining the stability of the crystal structure, reducing volume changes during charging and discharging, and improving the compressive strength and electronic conductivity of the particles.

[0040] In some embodiments, the positive electrode material is subjected to XRD measurement using Cu-Kα rays, and the positive electrode material unit cell parameter ratio is c / a, c / a>4.92. c / a can be 4.921, 4.925, 4.93, 4.94, 4.95, 4.96, 4.98 or 4.99, etc., which is not limited here.

[0041] In the present application, the unit cell parameter ratio c / a of the positive electrode material is within the above range, which indicates that the crystal structure of the positive electrode material is stable, the internal doping of the positive electrode material is uniform, and the internal defects of the positive electrode material crystal can be reduced, which is beneficial to the improvement of the capacity of the positive electrode material.

[0042] In some embodiments, the volume particle size distribution width of the positive electrode material satisfies: 1.0≤(D 90 -D 10 ) / D 50 ≤1.5, specifically can be 1.0, 1.05, 1.1, 1.15, 1.18, 1.2, 1.22, 1.25, 1.26, 1.3, 1.35, 1.4 or 1.5, etc., of course, it can also be other values ​​within the above range, which is not limited here. In the present application, by controlling the particle size distribution width of the positive electrode material within the above range, particles of different sizes can be stacked more closely, so that the compaction density of the positive electrode sheet is improved and the energy density is higher.

[0043] In some embodiments, the positive electrode material is a single crystal material, and the positive electrode material includes single crystal particles, and the single crystal particles are particles with the same orientation. It should be specially noted that the "single crystal material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in reality. Therefore, the single crystal materials known in the art are actually more "single crystal morphology" positive electrode materials, which only show a single crystal-like large particle size in size, which is different from polycrystalline particles composed of many small particles.

[0044] The single crystal grain in the present application may be a single particle composed of one primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several primary particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope.

[0045] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.

[0046] In some embodiments, the average particle size of the crystal grains is 1 μm to 5 μm, specifically 1.0 μm, 2.0 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Since the average particle size of the crystal grains is within the above range, the crystal grains within this size range have better electrochemical properties, higher discharge capacity and excellent rate performance.

[0047] In some embodiments, the specific surface area of ​​the positive electrode material is 0.4 m 2 / g~0.9m 2 / g; specifically, it can be 0.4m 2 / g, 0.45m 2 / g, 0.5m 2 / g, 0.55m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.7m 2 / g, 0.75m 2 / g, 0.8m 2 / g, 0.85m 2 / g or 0.9m 2 / g, etc., and of course, other values ​​within the above range may also be possible, which are not limited here. The specific surface area of ​​the positive electrode material can be controlled within the above range, which can effectively reduce the side reaction between the positive electrode material and the electrolyte and improve the capacity of the positive electrode material.

[0048] In some embodiments, the tap density of the positive electrode material is ρ1 g / cm 3 , 2.0<ρ1<2.5, specifically 2.01g / cm 3 , 2.05g / cm 3 , 2.1g / cm 3 , 2.25g / cm 3 , 2.3g / cm 3 , 2.35g / cm 3 , 2.4g / cm 3 or 2.49 g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here.

[0049] In some embodiments, the compaction density of the positive electrode material is p2 g / cm 3 , 2.8≤ρ2<3.6. Specifically, it can be 2.8g / cm 3 , 2.9g / cm 3 、3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3, 3.25g / cm 3 、3.3g / cm 3 、3.35g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 or 3.59 g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here.

[0050] In some embodiments, the gas production value of the positive electrode material is less than or equal to 1 mL / g, and can be specifically 0.1 mL / g, 0.2 mL / g, 0.3 mL / g, 0.4 mL / g, 0.5 mL / g, 0.6 mL / g, 0.7 mL / g, 0.8 mL / g or 1 mL / g, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0051] In some embodiments, the lithium-nickel mixing rate of the positive electrode material is 1% to 4%, specifically 1%, 1.2%, 1.5%, 1.8%, 2.0%, 2.4%, 2.8%, 3.0%, 3.2%, 3.4%, 3.8% or 4%, etc., and of course, it can also be other values ​​within the above range, which are not limited here. It can be understood that when the lithium-nickel mixing rate of the positive electrode material is too high, some nickel ions will occupy the original position of lithium ions, destroy the orderliness of the crystal structure, cause lattice distortion, reduce the number of lithium ions to be deintercalated, and reduce capacity. The present application controls the lithium-nickel mixing rate within the above range, which can reduce lattice distortion, reduce the local stress aggravation caused by the lithium ion deintercalation process, improve the particle structure stability of the positive electrode material, reduce particle rupture, improve the reversible discharge capacity of the positive electrode material, and improve the cycle life of the battery.

[0052] In some embodiments, the SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and 200 particles in the SEM image are randomly measured. The average size of the longest diameter of a single particle is D, and the average size of the straight line side that perpendicularly divides the longest diameter of the particle is L. The average aspect ratio of the particle is α=D / L, 1≤α≤1.6, which can be 1, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55 or 1.6, etc., and of course, it can also be other values ​​within the above range, which is not limited here. When the average aspect ratio of the particles is within the above range, the particles have a high degree of roundness and no obvious edges and corners, which is beneficial to reducing the specific surface area of ​​the positive electrode material, reducing the direct contact between the positive electrode material and the electrolyte, and reducing the occurrence of side reactions; and the aspect ratio is controlled within the above range, which is beneficial to the uniform dispersion of the particle expansion stress and the reduction of local stress accumulation. The present application synergistically controls the average aspect ratio of the particles and the number of particles with cracks, which can further reduce the occurrence of side reactions between the electrolyte and the positive electrode material and improve the structural stability and cycle stability of the positive electrode material.

[0053] In a second aspect, the present application provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:

[0054] Step S10, prepare nickel, manganese, and cobalt salt solutions, prepare a mixed solution according to a certain stoichiometric ratio, and then add an appropriate amount of complexing agent so that the concentration of the complexing agent in the mixed solution is 0.2 mol / L to 3 mol / L. The positive electrode material precursor is prepared by using a spray pyrolysis process, and the pyrolysis temperature T and the atomized droplet diameter d are controlled to satisfy T=(2000+600d) / (d+2).

[0055] In some embodiments, the stoichiometric ratio of nickel, cobalt, and manganese meets the following conditions: 0.8≤Ni≤0.95, 0≤Co≤0.2, 0≤Mn≤0.2.

[0056] In some embodiments, the salt solution is at least one of nitrate, hydrochloride, sulfate, carbonate, oxalate, and acetate. For example, the nickel salt solution can be at least one of nickel chloride, nickel sulfate, nickel nitrate, nickel carbonate, nickel oxalate, and nickel acetate. Of course, nickel, manganese, and cobalt can also be metal elemental raw materials or recycled materials of ternary positive electrode materials, which are not limited here.

[0057] In some embodiments, the complexing agent includes at least one of citric acid, tartaric acid, chitosan, polyvinyl pyrrolidone, and acetylacetone.

[0058] In some embodiments, the complexing agent is added to the mixed solution twice, and the time interval between the two additions is 1 hour to 6 hours.

[0059] In some embodiments, the concentration of the complexing agent in the mixed solution is 0.2mol / L to 3mol / L, specifically 0.2mol / L, 0.4mol / L, 0.5mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.2mol / L, 1.3mol / L, 1.5mol / L, 1.8mol / L, 2.0mol / L, 2.2mol / L, 2.5mol / L, 2.8mol / L or 3.0mol / L, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0060] It should be noted that the addition of different types of chelating agents can form complexes with metal ions in the salt solution, thereby optimizing the crystal structure of the cathode material precursor, promoting the directional growth of the crystal structure toward the (003) crystal plane, making the layered structure of the cathode material precursor more stable, and improving the diffusion efficiency of lithium ions.

[0061] In some embodiments, the pyrolysis temperature T and the atomized droplet diameter d are controlled to satisfy T=(2000+600d) / (d+2).

[0062] In some embodiments, the atomization flow rate of the mixed solution during spray pyrolysis is 5 L / min to 20 L / min, specifically 5 L / min, 8 L / min, 10 L / min, 12 L / min, 15 L / min, 18 L / min or 20 L / min, etc. Of course, it can also be other values ​​within the above range, which are not limited here.

[0063] In some embodiments, a compound containing element M is further added to the mixed solution according to a target doping ratio, which may specifically be a nitrate containing element M, a hydrochloride containing element M, an acid containing element M, etc., which is not limited here.

[0064] In some embodiments, the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn, and Y.

[0065] Step S20, mixing the positive electrode material precursor, the lithium source, and the dopant to obtain a first mixture, and performing a primary sintering treatment on the first mixture to obtain a primary sintered product.

[0066] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate, and lithium oxalate.

[0067] In some embodiments, the ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal in the nickel-cobalt-manganese-based oxide precursor is controlled to be 1.0≤n Li / nMe ≤1.1; specifically, it can be 1.0:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1 or 1.1:1, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0068] In some embodiments, the dopant includes a compound containing an M element, and the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.

[0069] In some embodiments, the first mixture further includes a flux, and the flux includes at least one of SrO, SrCO3, WO3, and TiO2. The flux has a relatively low melting point, which helps the growth of single crystal particles and repairs cracks formed during the growth process. The flux accelerates the growth of single crystals in the early stage of the primary sintering process, helps repair intercrystalline cracks of particles in the later stage of the primary sintering process, and helps the primary sintering product become rounded and dispersed single crystal particles.

[0070] In some embodiments, based on the mass of the positive electrode material precursor as 100%, the amount of flux added is 0.03% to 1%, specifically 0.03%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.5%, 0.8% or 1.0%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] In some embodiments, the mixing is performed in a mixing device, which may be a high-speed mixer, a ball mill mixer, a VC mixer, or a three-dimensional mixer, etc. The device may be selected according to actual needs and is not limited here.

[0072] In some embodiments, the primary sintering process is performed in an oxygen-containing atmosphere, and the oxygen concentration in the oxygen-containing atmosphere is ≥ 95%.

[0073] In some embodiments, a sintering process includes a first stage, a second stage and a third stage performed in sequence, the sintering temperature T1 of the first stage is 500°C to 600°C, the sintering temperature T2 of the second stage is 700°C to 800°C, and the sintering temperature T3 of the third stage is 800°C to 900°C.

[0074] In some embodiments, the temperature of the first stage is 500°C to 600°C, specifically 500°C, 520°C, 530°C, 550°C, 570°C, 580°C or 600°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0075] In some embodiments, the duration of the first stage is 1 h to 4 h, specifically 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0076] In some embodiments, the temperature of the second stage is 700°C to 800°C, specifically 700°C, 720°C, 730°C, 750°C, 770°C, 780°C or 800°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0077] In some embodiments, the duration of the second stage is 1 h to 4 h, specifically 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0078] In some embodiments, the temperature of the third stage is 780°C to 900°C, specifically 780°C, 800°C, 820°C, 830°C, 850°C, 870°C, 880°C or 900°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0079] In some embodiments, the duration of the second stage is 5 h to 10 h, specifically 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0080] Step S30, air flow pulverizing the primary sintered product, mixing the air flow pulverized product with a coating agent, and then performing a secondary sintering treatment to obtain a positive electrode material.

[0081] In some embodiments, during the air flow crushing process, the weight of the grinding body is controlled to be 20-60% of the design upper limit of the equipment grinding body weight, which can be specifically 20%, 30%, 40%, 50%, 55% or 60%, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0082] In some embodiments, during the air flow pulverizing process, the pulverizing air pressure is controlled at 0.4 MPa to 0.65 MPa, specifically 0.4 MPa, 0.5 MPa, 0.55 MPa, 0.6 MPa or 0.65 MPa, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0083] In some embodiments, during the air flow pulverization process, the grading frequency of the air flow pulverization is controlled to be 50 Hz to 100 Hz, specifically 50 Hz, 60 Hz, 70 Hz, 80 Hz, 95 Hz or 100 Hz, etc., and of course other values ​​within the above range are also possible, which are not limited here.

[0084] In some embodiments, the average aspect ratio of the material after the jet milling process is 1 to 1.6.

[0085] In some embodiments, based on the mass of the pulverized product as 100%, the amount of the coating agent added is 0.05% to 0.4%, specifically 0.05%, 0.06%, 0.07%, 0.08%, 0.1%, 0.12%, 0.15%, 0.2%, 0.25%, 0.28%, 0.3%, 0.35% or 0.4%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0086] In some embodiments, the coating agent includes a compound containing a N element, and the N element includes at least one of Zr, Ti, Al, W, and Mg.

[0087] In some embodiments, the coating treatment is carried out under stirring, and the stirring speed is controlled to be 100rpm to 700rpm, specifically 100rpm, 150rpm, 250rpm, 350rpm, 400rpm, 450rpm, 550rpm, 650rpm or 700rpm, etc. Of course, it can also be other values ​​within the above range, which are not limited here. Preferably, the stirring speed is 450rpm.

[0088] In some embodiments, the oxygen concentration in the oxygen-containing atmosphere is ≥ 95%.

[0089] In some embodiments, the temperature of the secondary sintering treatment is 350°C to 600°C, specifically 350°C, 360°C, 380°C, 400°C, 420°C, 480°C, 500°C, 550°C or 600°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0090] In some embodiments, the secondary sintering treatment time is 5 h to 10 h, specifically 5 h, 5.5 h, 6 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h or 10 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0091] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.

[0092] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery.

[0093] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.

[0094] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a shell and an electrode assembly, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence.

[0095] In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.

[0096] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one surface of the positive electrode current collector 11 .

[0097] In some embodiments, the positive electrode current collector 11 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 12 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.

[0098] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector.

[0099] In some embodiments, the negative electrode current collector 21 can be made of at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or can be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.

[0100] In some embodiments, the negative electrode active material layer 22 includes a negative electrode material, and the negative electrode material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0101] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.

[0102] Example 1

[0103] (1) Dissolve metal nickel, cobalt and manganese in nitric acid in a molar ratio of 90:5:5 to form a uniform mixed solution, disperse the mixed solution by ultrasonication for 2 hours, add citric acid as a complexing agent in two times, the interval between the first and second additions is 1 hour, and the final concentration of citric acid in the mixed solution is 1 mol / L, spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the size of the atomized droplets to 15 μm, and the pyrolysis temperature to 733°C to obtain Ni 0.9 Co 0.05 Mn 0.05 O precursor.

[0104] (2) 300g of precursor Ni 0.9 Co 0.05 Mn 0.05 O, 198g LiOH, and 1.3g TiO2 are mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering includes three stages of sintering, and the temperature and time are respectively 500°C / 1.5h, 720°C / 2h, and 800°C / 8h; after sintering, the temperature is slowly annealed and cooled, and the cooling rate is 1.5°C / minute to obtain a primary sintering product.

[0105] (3) The primary sintered product was subjected to air flow milling, the grinding body weight was controlled to be 1200 g, the air pressure of the air flow milling was controlled to be 0.65 MPa, the classification frequency was controlled to be 100 Hz, and the median particle size D50 of the air flow milling product was 4.12 μm.

[0106] (4) 100 g of the airflow pulverized product was mixed with 0.2 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 510°C. After screening, the positive electrode material was obtained.

[0107] The general chemical formula of the positive electrode material prepared in this embodiment is: LiNi 0.9 Co 0.05 Mn 0.05 O2, in which the metal elements include Ti and Al. Since the amount of metal elements is difficult to determine accurately, they are not reflected in the chemical formula.

[0108] Example 2

[0109] (1) Dissolve metal nickel, cobalt and manganese in nitric acid in a molar ratio of 80:10:10 to form a uniform mixed solution, disperse the mixed solution by ultrasonication for 3 h, add citric acid as a complexing agent, add it twice, the interval between the first addition and the second addition is 1 h, and the final concentration of citric acid in the mixed solution is 1 mol / L, spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the size of the atomized droplets to 15 μm, and the pyrolysis temperature to 733 ° C, to obtain Ni 0.8 Co 0.1 Mn 0.1 O precursor.

[0110] (2) 300g of precursor Ni 0.8 Co 0.1 Mn 0.1 O, 201g Li2CO3, and 1.4g TiO2 are uniformly mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering is a three-stage sintering, and the temperature and time are respectively 500℃ / 1.5h, 760℃ / 2h, and 880℃ / 8h; after sintering, the temperature is slowly annealed and cooled, and the cooling rate is 1.5℃ / min to obtain a primary sintering product.

[0111] (3) The primary sintered product was subjected to air flow milling, the grinding body weight was controlled to be 1200 g, the air pressure of the air flow milling was controlled to be 0.65 MPa, the classification frequency was controlled to be 95 Hz, and the median particle size D50 of the air flow milling product was 4.05 μm.

[0112] (4) 100 g of the airflow pulverized product was mixed with 0.2 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 510°C. After screening, the positive electrode material was obtained.

[0113] Example 3

[0114] (1) Dissolve metal nickel and cobalt in nitric acid at a molar ratio of 90:10 to form a uniform mixed solution, disperse the mixed solution by ultrasonication for 3 h, add citric acid as a complexing agent in two additions, the interval between the first addition and the second addition is 1 h, and the final concentration of citric acid in the mixed solution is 1 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the size of the atomized droplets to 15 μm, and the pyrolysis temperature to 733 ° C, to obtain Ni 0.9 Co 0.1 O precursor.

[0115] (2) 300g of precursor Ni 0.9 Co 0.1O, 197g LiOH, and 1.3g TiO2 are uniformly mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering is divided into three stages, and the temperatures are 500°C / 1.5h, 720°C / 2h, and 790°C / 8h respectively; after sintering, the temperature is slowly annealed and cooled, and the cooling rate is 1.5°C / min to obtain a primary sintering product.

[0116] (3) The primary sintered product was subjected to air flow milling, the grinding body weight was controlled to be 1200 g, the air pressure of the air flow milling was controlled to be 0.65 MPa, the classification frequency was controlled to be 95 Hz, and the median particle size D50 of the air flow milling product was 4.15 μm.

[0117] (4) 100 g of the airflow pulverized product was mixed with 0.2 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 510°C. After screening, the positive electrode material was obtained.

[0118] Example 4

[0119] The difference from Example 1 is:

[0120] (2) 300g Ni 0.9 Co 0.05 Mn 0.05 O, 198g LiOH, 1.3g TiO2, and 2g SrCO3 are uniformly mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering is divided into three stages, and the temperatures are 500°C / 1.5h, 760°C / 4h, and 790°C / 10h respectively; after sintering, the temperature is slowly annealed and cooled, and the cooling rate is 1.5°C / min to obtain a primary sintering product.

[0121] Example 5

[0122] The difference from Example 1 is:

[0123] (2) 300g Ni 0.9 Co 0.05 Mn 0.05 O and 198g LiOH are uniformly mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering is divided into three stages, and the temperatures are 500°C / 1.5h, 720°C / 2h, and 760°C / 8h respectively; after sintering, the temperature is slowly annealed and cooled, and the cooling rate is 1.5°C / min to obtain a primary sintering product.

[0124] Example 6

[0125] The difference from Example 1 is:

[0126] (1) Dissolve metal nickel, cobalt and manganese in nitric acid in a molar ratio of 90:5:5 to form a uniform mixed solution, disperse the mixed solution by ultrasonication for 2 h, add citric acid as a complexing agent, add it twice, the interval between the first addition and the second addition is 1 h, and the final concentration of citric acid in the mixed solution is 1 mol / L, spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the size of the atomized droplets to 20 μm, and the pyrolysis temperature to 700 ° C, to obtain Ni 0.9 Co 0.05 Mn 0.05 O precursor.

[0127] (2) 300g Ni 0.9 Co 0.05 Mn 0.05 O, 198g LiOH, and 1.3g TiO2 are uniformly mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering is divided into three stages, and the temperatures are 500°C / 1.5h, 700°C / 2h, and 790°C / 8h respectively; after sintering, the temperature is slowly annealed and cooled, and the cooling rate is 1.5°C / min to obtain a primary sintering product.

[0128] Example 7

[0129] The difference from Example 1 is:

[0130] (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 90:5:5 to form a uniform mixed solution, disperse the mixed solution by ultrasonication for 2 h, add polyvinyl pyrrolidone as a complexing agent, add it twice, the interval between the first addition and the second addition is 1 h, the concentration of citric acid in the final mixed solution is 1 mol / L, spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the size of the atomized droplets to 10 μm, and the pyrolysis temperature to 800 ° C, to obtain Ni 0.9 Co 0.05 Mn 0.05 O precursor.

[0131] (2) 300g Ni 0.9 Co 0.05 Mn 0.05 O, 198g LiOH, and 1.3g TiO2 are uniformly mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering is divided into three stages, and the temperatures are 500°C / 1.5h, 720°C / 2h, and 780°C / 8h respectively; after sintering, the temperature is slowly annealed and cooled, and the cooling rate is 1.5°C / min to obtain a primary sintering product.

[0132] Example 8

[0133] The difference from Example 1 is:

[0134] (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 90:5:5 to form a uniform mixed solution, first disperse the mixed solution by ultrasonication for 2 h, add acetylacetone as a complexing agent in two times, with an interval of 1 h between the first and second additions, and then spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the size of the atomized droplets to 10 μm, and the pyrolysis temperature to 800 ° C, to obtain Ni 0.9 Co 0.05 Mn 0.05 O precursor.

[0135] Example 9

[0136] (1) Dissolve metal nickel and manganese in nitric acid at a molar ratio of 96:4 to form a uniform mixed solution, disperse the mixed solution by ultrasonication for 3 h, add citric acid as a complexing agent, add it twice, the interval between the first and second additions is 1 h, and the final concentration of citric acid in the mixed solution is 1 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the size of the atomized droplets to 15 μm, and the pyrolysis temperature to 733 ° C to obtain the precursor Ni 0.96 Mn 0.04 O.

[0137] (2) 300g of precursor Ni 0.96 Mn 0.04 O2 and 192g LiOH were uniformly mixed to obtain a first mixture. The first mixture was placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering was three-stage sintering at temperatures of 500°C / 1.5h, 720°C / 2h, and 780°C / 8h; after sintering, the mixture was slowly annealed and cooled at a cooling rate of 1.5°C / min to obtain a primary sintering product.

[0138] (3) The primary sintered product was subjected to air flow milling, the grinding body weight was controlled to be 1200 g, the air pressure of the air flow milling was controlled to be 0.65 MPa, the classification frequency was controlled to be 95 Hz, and the median particle size D50 of the air flow milling product was 4.15 μm.

[0139] (4) 100 g of the airflow pulverized product was mixed with 0.2 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 510°C. After screening, the positive electrode material was obtained.

[0140] Example 10

[0141] (1) Dissolve metal nickel, cobalt and manganese in nitric acid in a molar ratio of 88:10:2 to form a uniform mixed solution, disperse the mixed solution by ultrasonication for 3 h, add citric acid as a complexing agent, add it twice, the interval between the first addition and the second addition is 1 h, and the final concentration of citric acid in the mixed solution is 1 mol / L, spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the size of the atomized droplets to 15 μm, and the pyrolysis temperature to 733 ° C, to obtain the precursor Ni 0.88 Co 0.1 Mn 0.02 O.

[0142] (2) 300g of precursor Ni 0.88 Co 0.1 Mn 0.02 O, 213g LiOH, and 1.4g TiO2 are uniformly mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering is divided into three stages, and the temperatures are 500°C / 1.5h, 730°C / 2h, and 800°C / 8h respectively; after sintering, the temperature is slowly annealed and cooled, and the cooling rate is 1.5°C / min to obtain a primary sintering product.

[0143] (3) The primary sintered product was subjected to air flow milling, the grinding body weight was controlled to be 1200 g, the air pressure of the air flow milling was controlled to be 0.65 MPa, the classification frequency was controlled to be 95 Hz, and the median particle size D50 of the air flow milling product was 4.15 μm.

[0144] (4) 100 g of the airflow pulverized product was mixed with 0.2 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 510°C. After screening, the positive electrode material was obtained.

[0145] Embodiment 11

[0146] The difference between this embodiment and embodiment 2 is that:

[0147] (2) 300g of precursor Ni 0.8 Co 0.1 Al 0.1 O, 208g LiOH, and 1.3g TiO2 are uniformly mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering is divided into three stages, and the temperatures are 500°C / 1.5h, 760°C / 2h, and 830°C / 8h respectively; after sintering, the temperature is slowly annealed and cooled, and the cooling rate is 1.5°C / min to obtain a primary sintering product.

[0148] Example 12

[0149] The difference between this embodiment and embodiment 2 is that:

[0150] (2) 300g Ni 0.8 Co 0.1 Mn 0.1 O, 201g Li2CO3, and 1.4g TiO2 are uniformly mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, and the primary sintering is a three-stage sintering, and the temperature and time are respectively 500℃ / 2h, 780℃ / 4h, and 920℃ / 10h; after sintering, the temperature is slowly annealed and cooled, and the cooling rate is 1.5℃ / min to obtain a primary sintering product.

[0151] Comparative Example 1

[0152] (1) 300g Ni 0.88 Co 0.1 Mn 0.02 O, 213g LiOH, and 1.4g TiO2 were uniformly mixed to obtain a first mixture. The first mixture was placed in an oxygen atmosphere furnace for primary sintering at a temperature of 890°C for 4 hours, and after sintering, the temperature was rapidly annealed and cooled at a cooling rate of 8°C / min to obtain a primary sintering product.

[0153] (2) The primary sintered product was subjected to air flow milling, the grinding body weight was controlled to be 1200 g, the air pressure of the air flow milling was controlled to be 0.65 MPa, the classification frequency was controlled to be 95 Hz, and the median particle size D50 of the air flow milling product was 4.08 μm.

[0154] (3) 100 g of the airflow pulverized product was mixed with 0.2 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 510°C. After screening, the positive electrode material was obtained.

[0155] Comparative Example 2

[0156] The difference from Example 2 is that:

[0157] (2) 300g Ni 0.8 Co 0.1 Mn 0.1 O, 201g Li2CO3, and 1.4g TiO2 were uniformly mixed to obtain a first mixture. The first mixture was placed in an oxygen atmosphere furnace for primary sintering at a temperature of 900°C for 4 hours, and after sintering, the temperature was rapidly annealed and cooled at a cooling rate of 8°C / min to obtain a primary sintering product.

[0158] (3) The primary sintered product was subjected to air flow milling, the grinding body weight was controlled to be 1200 g, the air pressure of the air flow milling was controlled to be 0.65 MPa, the classification frequency was controlled to be 95 Hz, and the median particle size D50 of the air flow milling product was 4.05 μm.

[0159] Comparative Example 3

[0160] The difference from Example 2 is that:

[0161] (2) 300g Ni 0.8 Co 0.1 Mn 0.1 O, 201g Li2CO3, and 1.4g TiO2 are uniformly mixed to obtain a first mixture. The first mixture is placed in an oxygen atmosphere furnace for primary sintering, the primary sintering is three-stage sintering, the temperatures are 500℃ / 1.5h, 760℃ / 2h, and 880℃ / 8h, respectively, and after sintering, rapid annealing and cooling are performed at a cooling rate of 8℃ / min to obtain a primary sintering product.

[0162] (3) The primary sintered product was subjected to air flow milling, the grinding body weight was controlled to be 1200 g, the air pressure of the air flow milling was controlled to be 0.65 MPa, the classification frequency was controlled to be 95 Hz, and the median particle size D50 of the air flow milling product was 4.11 μm.

[0163] Test method:

[0164] (1) Particle distribution test of positive electrode materials:

[0165] The particle size in the SEM image was calculated using Nana Measure software. More than 200 particles in the SEM image were randomly measured. The average size of the longest diameter of a single particle was D, the average size of the straight line side that perpendicularly bisected the longest diameter of the particle was L, and the average aspect ratio of the particle was α=D / L.

[0166] (2) Testing of metal elements in positive electrode materials:

[0167] Take 0.3g of the sample to be tested and dissolve it in aqua regia, cool and dilute to a volume of 100ml to prepare the mother solution for determination; take 1mL of the mother solution for determination, dilute it 100 times, and test the content of the main elements Li, Ni, Co, and Mn and the content of other elements such as metal elements by ICP. The determination adopts Agilent 5110ICP-OES detection equipment.

[0168] (3) Particle size test:

[0169] The particle size distribution of the positive electrode material particles was obtained by using the laser diffraction light intensity distribution of the British Malvern Mastersizer 3000 model laser particle size analyzer. The volume-based cumulative particle size distribution of the particle size distribution determination was measured by the laser diffraction method, D 10 It indicates the particle size corresponding to the cumulative particle size distribution percentage of the powder reaching 10%, D 50 Indicates the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, D 90It indicates the particle size corresponding to when the cumulative particle size distribution percentage reaches 90%.

[0170] Volume particle size distribution width of positive electrode material = (D 90 -D 10 ) / D 50 .

[0171] (4) Specific surface area test:

[0172] The specific surface area of ​​the material was calculated using the American TriStar II specific surface and pore analyzer by nitrogen adsorption and the BET method.

[0173] (5) Average particle size test:

[0174] Hitachi S4800 scanning electron microscope was used to take 5 views of the sample at different positions at 3000 times magnification, and Nano Measure software was used to measure the particle size of the positive electrode material in each view. The average value of the 5 particle sizes was taken as the average particle size of the particles.

[0175] (6) Tap density test of positive electrode material:

[0176] Test of tap density ρ1: Dandong Better BT-303 was used to test the tap density, with a vibration rate of 3000 times / min, a vibration time of 1min, and a vibration amplitude of 3mm±0.1mm.

[0177] (7) Compacted density test of positive electrode materials:

[0178] The compaction density ρ2 of the powder was tested using a compaction density meter with a pressure of 6t for 30s.

[0179] (8) XRD test analysis of positive electrode materials:

[0180] The diffraction peak of the material is tested by XRD diffractometer, with a scanning speed of 1° / min, a step length of 0.005°, and a scanning range of 10-70° to obtain the diffraction peak of the material, and then the strain value of the ternary positive electrode material is calculated and output through XRD refinement of the diffraction peak. In the XRD refinement process, the calculation of microscopic strain and grain size is one of the key steps.

[0181] First, according to the Bragg equation and Scherrer formula, the calculation formula becomes: By analyzing β s and β D, which can be used to describe the degree of FWHM widening caused by strain. In the Rietveld refinement process, the pseudo-Voigt function is used to represent the half-height width (FWHM) of the diffraction peak shape function. The formula is divided into two parts: Gaussian and Lorentzian, which contain parameters related to microscopic strain and grain size respectively. The specific formula is: Gaussian part: Lorentz part: Among them, U and Y are parameters related to microscopic strain, X and P are parameters related to grain size, and these parameters correspond to the peak shape correction parameters GU, LY, LX and GP in the refinement process. Therefore, the lattice strain parameters can be obtained by deriving these four parameters after refining the peak shape of the measured XRD data and substituting them into the corresponding calculation formula.

[0182] The XRD diffractometer was used to test in the range of 10°-70° at 1° / min and a step size of 0.005°; the tested XRD image was then subjected to Rietveld refinement using GASA software, with the refinement standard being RWP < 3%; after refinement, the unit cell volume, cell parameters c, a and cation mixing information can be obtained in the GSAS software cell parameter interface.

[0183] (9) The test method for the percentage of particles with cracks in the positive electrode material is as follows:

[0184] Test on the proportion of particles with microcracks in positive electrode materials: First, take the powder positive electrode material, mix the powder positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, add NMP (N-methylpyrrolidone) to make a uniform slurry and apply it on aluminum foil, dry it in an oven, and make a pole piece. Use the pole piece as a sample, and according to the standardized process of cross-section sample preparation, use an electron transmission microscope to focus the ion beam into a small-sized ion beam to bombard the surface of the sample to achieve sample peeling. The stripped sample is tested by a scanning electron microscope (SEM). Under a field of view of 5k, the field of view of different areas is counted, and the proportion of the number of positive electrode material particles with microcracks to the total number of positive electrode material particles is counted, and the number of microcracks is characterized by the proportion. The test results of this application are the statistical results obtained by randomly selecting the cross-sections of about 300 positive electrode material particles in the SEM image as samples. The SEM test requires random sampling of positive electrode materials and random selection of areas. The SEM images obtained from the test can represent the average level of the positive electrode materials tested. Since the pole pieces are not rolled during the production process in this test method, the percentage of microcracks obtained from the test can be regarded as the percentage of microcrack particles in the positive electrode material in powder state.

[0185] (10) Electrochemical performance evaluation using button half-cell:

[0186] After the positive electrode material is mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, NMP (N-methylpyrrolidone) is added to make a uniform slurry, the slurry is evenly coated on aluminum foil and placed in a 100°C oven for drying for 12 hours. After drying, it is rolled at a pressure of 10Mpa and cut into a circular pole piece with a diameter of 14mm. The negative electrode uses a Li metal sheet with a diameter of 14mm. The lithium-ion battery is assembled according to the CR2025 button battery in industry. The diaphragm is a Cellgard diaphragm, and the electrolyte uses an equal amount of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1mol / L LiPF6 as the electrolyte. The positive pole piece, diaphragm, negative pole piece and electrolyte are assembled into a button battery in an Ar gas glove box with a water content and an oxygen content of less than 0.5ppm.

[0187] Capacity test system: The blue electric test system is used for electrical performance testing (charge and discharge voltage is 3.0~4.3V, temperature condition is 25℃), 0.1C charging, 0.1C discharging, constant voltage cut-off current is 0.005C, and the discharge capacity mAh / g is calculated.

[0188] Cycle test system: At 25°C, charge and discharge voltage is 3.0-4.3V, charge and discharge cycle is 0.5C / 1C for 50 cycles, and the final capacity retention rate after 50 cycles is the cycle performance.

[0189] (11) Gas generation value test of positive electrode materials:

[0190] The positive electrode materials were assembled into a 2Ah soft-pack battery, in which the positive electrode formula was positive electrode: binder: conductive agent = 96.8:1.2:2, and the negative electrode formula was negative electrode (artificial graphite): binder: conductive agent = 95.6:1.4:3; the batteries were stored in a high-temperature oven at 60°C for 7 days, and the gas production was tested by the drainage method. The obtained gas production was the 7-day gas production of the soft-pack battery per unit mass, and the unit was mL / g.

[0191] The positive electrode materials of the above embodiments (abbreviated as S1 to S12) and comparative examples (abbreviated as D1 to D3) were subjected to physical and chemical performance tests and electrochemical tests. The above test results are detailed in Tables 1 to 2.

[0192] Table 1 Physical and chemical performance parameters of positive electrode materials

[0193]

[0194]

[0195] Table 2 Electrochemical performance results of positive electrode materials

[0196]

[0197] Figure 2 and Figure 3 The cross-sectional SEM images of Example 1 and Comparative Example 1 at 5000 times magnification are shown in Figure 1. Figure 2 It can be seen that among the positive electrode materials obtained in Example 1, only two particles have cracks, and the number of particles with cracks accounts for a small proportion; Figure 3 It can be seen that among the positive electrode materials obtained in Comparative Example 1, there are 6 particles with cracks, and the number of particles with cracks accounts for a relatively large proportion.

[0198] According to the test data of Examples 1 to 12, the present application controls the unit cell volume of the positive electrode material and the number of cracks in the particles, and the two are controlled synergistically, which can effectively improve the crystal structure stability of the positive electrode material, reduce particle breakage, and improve the cycle stability of the positive electrode material. The unit cell parameter c / a of the positive electrode material is then adjusted to enhance the rate performance of the positive electrode material, thereby achieving a comprehensive improvement in the cycle stability and gas production of the positive electrode material.

[0199] According to the test data of Example 1, Example 2 and Example 3, as the composition of the transition metal in the positive electrode material changes, the capacity of the positive electrode material fluctuates slightly, but the cycle capacity retention rate, gas production value and rate performance of the positive electrode material can be stabilized at a relatively good level.

[0200] According to the test data of Example 1, Example 4 and Example 5, the addition of an appropriate amount of flux can help the growth of particles and repair cracks formed in the particles during the growth process. The number of cracked particles in the positive electrode material of Example 4 accounts for a relatively small proportion. Therefore, the capacity retention rate and gas production value of the positive electrode materials of Example 1 and Example 4 are better than those of Example 5.

[0201] According to the test data of Example 1 and Examples 6 to 8, the addition of different types of complexing agents can form complexes with metal ions, optimize the crystal structure of the positive electrode material, promote the directional growth of the crystal structure toward the (003) crystal plane, make the layered structure of the positive electrode material precursor more stable, and improve the diffusion efficiency of lithium ions. Therefore, the battery prepared by the positive electrode materials of Example 1 and Examples 6 to 8 can also maintain a good level of cycle capacity retention and gas production value.

[0202] According to the test data of Example 1 and Example 9, the lithium-nickel mixing rate of the lithium nickel cobalt oxide positive electrode material is increased compared with that of Example 1, and the gas generation value and capacity retention rate of the positive electrode material are slightly affected.

[0203] According to the test data of Example 1 and Example 10, as the nickel content in the positive electrode material decreases, the discharge capacity of the positive electrode material will also decrease, and the proportion of particles with cracks in the positive electrode material of Example 10 increases. Therefore, the cycle capacity retention rate of the positive electrode material also decreases slightly.

[0204] According to the test data of Example 2, Example 11 and Example 12, the primary sintering temperature used in Example 11 is slightly lower than that in Example 2, the number of cracked particles in the positive electrode material accounts for a small proportion, the cycle capacity retention rate is slightly higher than that in Example 2, and the gas production is reduced. The primary sintering temperature used in Example 12 is slightly higher than that in Example 2, resulting in increased internal stress in some particles of the positive electrode material, an increase in the number of cracked particles in the positive electrode material, a slight decrease in the cycle capacity retention rate compared to Example 2, and an increase in gas production.

[0205] According to the test data of Example 10 and Comparative Example 1, Comparative Example 1 does not have a multi-stage sintering process, resulting in that the internal stress of the particles cannot be fully released during the sintering process, and the number of particles with cracks in the positive electrode material is significantly increased, which accelerates the capacity decay of the positive electrode material, intensifies gas production, and significantly reduces the capacity retention rate.

[0206] According to the test data of Example 2 and Comparative Example 2, Comparative Example 2 does not adopt a multi-stage sintering process, the cell parameter c / a of the positive electrode material is too small, the lithium-nickel mixing rate of the positive electrode material increases, and the stress generated by the sintering of the positive electrode material causes the positive electrode material to be more likely to produce internal cracks during the collision process during the crushing process. A smaller c / a value means a poor layered structure, which will lead to a decrease in the capacity of the positive electrode material, and more internal cracks will lead to an increase in the gas production of the positive electrode material.

[0207] According to the test data of Example 2 and Comparative Example 3, the primary sintering temperature is too low, resulting in an excessively large unit cell volume of the positive electrode material, smaller unit cell parameters, more defects in the layered structure of the positive electrode material, an increase in the lithium-nickel mixing rate of the positive electrode material, and a decrease in the capacity retention rate of the positive electrode material.

[0208] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A positive electrode material, characterized in that: The chemical formula of the positive electrode material is Li x Ni a Co b M c O2, 0.98≤x≤1.1, 0.8≤a≤0.98, 0≤b≤0.2, 0≤c≤0.2, a+b+c=1, b and c are not 0 at the same time, M is a metal element; A cross-sectional SEM image of the positive electrode material is measured at a magnification of 3K by a scanning electron microscope, and 300 particles in the cross-sectional SEM image are randomly measured, and the number of particles with cracks in the cross-sectional SEM image accounts for less than 10%; The positive electrode material is subjected to XRD measurement using Cu-Kα radiation, and the unit cell volume of the positive electrode material is The relationship between the unit cell parameter c of the c-axis and the unit cell parameter a of the a-axis of the positive electrode material satisfies: c / a>4.

92.

2. The positive electrode material according to claim 1, characterized in that The lithium-nickel mixing rate of the positive electrode material is 1% to 4%.

3. The positive electrode material according to claim 1, characterized in that The lattice strain of the positive electrode material is less than 0.1%.

4. The positive electrode material according to claim 1, characterized in that The M element includes at least one of Mn, Al, Ti, Zr, Ca, Mg, W, Ba, La, Ce, B, and Y.

5. The positive electrode material according to claim 1, characterized in that The volume particle size distribution width of the positive electrode material satisfies: 1.0≤(D 90 -D 10 ) / D 50 ≤1.

5.

6. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, and the positive electrode material includes single crystal particles, and the particle size of the single crystal particles is 1 μm to 5 μm.

7. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The specific surface area of ​​the positive electrode material is 0.4 m 2 / g~0.9m 2 / g; (2) The tap density of the positive electrode material is ρ1g / cm 3 , 2.0<ρ1<2.5; (3) The compaction density of the positive electrode material is ρ2g / cm 3 , 2.8≤ρ2<3.

6.

8. The positive electrode material according to claim 1, characterized in that The gas generation value of the positive electrode material is less than or equal to 1 mL / g.

9. The positive electrode material according to any one of claims 1 to 8, characterized in that The SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and 200 particles in the SEM image are randomly measured. The average size of the longest diameter of a single particle is D, the average size of the straight line side that perpendicularly bisects the longest diameter of the particle is L, and the average aspect ratio of the particles is α=D / L, 1≤α≤1.

6.

10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nonaqueous Electrolyte Secondary Battery

    CN106067559A

  • Preparation method of large single crystal lithium ion battery nickel cobalt lithium manganate cathode material

    CN110534733A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN117199342A

  • Monocrystal ternary positive electrode material and preparation method and application thereof

    CN118782770A

  • Parallel processing apparatus and method for accelerated operation of artificial intelligence model

    KR102737303B1